Isolable zirconium hydride species in the reaction of amido complexes with amine–boranes. Issue 16 (22nd March 2017) - Greño, Maider; Mena, Miguel; Pérez-Redondo, Adrián; Yélamos, Carlos
Abstract : Mono-, di- and trinuclear zirconium hydride species have been isolated in the reaction of half-sandwich amido complexes with amine–borane adducts. Abstract : Mono-, di- and trinuclear zirconium hydride species have been isolated in the treatment of amido complexes [Zr(η 5 -C5 Me5 )(NMe2 ) n Cl3− n ] ( n = 3, 1) with amine–borane adducts NHR2 BH3 (R2 = Me2, H t Bu). The reactions involve the formation of amidoborane ligands with Zr⋯H–B interactions which readily undergo β-hydride elimination to give hydride functions.